Penerapan Model Pembelajaran Index Card Match Pada Mata Pelajaran Al-Qur’an Hadist Kelas IV Untuk Meningkatkan Motivasi Belajar Siswa Di Min Pahandut Palangka Raya - Lilik Kholisotin (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
Based on the observation of the learning process carried out in MIN Model Pahandut, actually the teacher in her teaching process still used a lecture method too much. The method is a conventional learning and the students are still a lot of listening. The situation still create a learning interactions that are still in one direction so that the less significant when viewed in terms of the effectiveness of the student which is reflected through attitudes, motivation to learn and an element of creativity. So that, the students tended to get bored and saturated because of the lack of a method that can provide motivation to the learning of students. Therefore, the writer interested in conducting a study on the implementation of learning method of index card match on the Al Qur'an Hadith subjects to improve the students’ motivation in MIN Model Palangka Raya. The purpose of this study was to know whether the teacher applied the learning methods of the index card match on the subjects of Al Qur’an Hadith in MIN Model Palangka Raya and to know how the implementation of the index card match method to improve the motivation of students’ learning. The approach used in this study is descriptive qualitative. To collect the data was done through observation, interviews and documentation, and then analyzed through the stages of data reduction, data presentation, and conclusions.